DISHARMONISASI PENGATURAN PENGELOLAAN PENGADAAN TANAH BAGI KEPENTINGAN PROYEK STRATEGIS NASIONAL - Gantika, Naldi; Novianti, Novianti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: Civil law in Indonesia is basically based on Napoleonic Law and then based on Staatsblaad Number 23 of 1847 concerning Burgerlijk Wetboek for Indonesia (abbreviated as BW) or referred to as the Civil Code. BW is actually a legal regulation made by the Dutch East Indies government aimed at non-native citizen groups, namely Europeans and Chinese. However, based on article 2 of the transitional regulations of the 1945 Constitution, it is written